The effects of capital structure change on security prices - Masulis, Ronald W. (Journal of Financial Economics, 1980)
This study considers the impact of capital structure change announcements on security prices. Statistically significant price adjustments in firms' common stock, preferred stock and debt related to these announcements are documented and alternative causes for these price changes are examined. The evidence is consistent with both corporate tax and wealth redistribution effects. There is also evidence that firms make decisions which do not maximize stockholder wealth. In addition, a new approach to testing the significance of public announcements on security returns is presented.